2021
DOI: 10.1177/15589250211061393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size of fumed silica on the puncture resistance of fabrics impregnated with shear thickening fluid

Abstract: This paper presents an investigation into the effect of particle size of fumed silica on the puncture resistance of fabric impregnated with shear thickening fluid (STF). Two different types of STF were fabricated from fumed silica nanoparticles with particle sizes of 12 and 40 nm respectively. The effects of the particle size and weight fraction of the fumed silica on the rheological property were studied. STFs impregnated woven fabrics were fabricated and tested for stabbing resistance. STFs made of fumed sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As indicated earlier, in most cases, the particle size and the long diameter of clusters of enhanced STF increase with the addition of ZnO. Recently, Grover, [ 41 ] Li [ 42 ] and Lu [ 43 ] suggested that the maximum viscosity decreases with the increase of nanoparticle size in the same volume fraction. The first reason was that the number of nanoparticles in the suspension decreased with the increase of the particle size.…”
Section: Resultsmentioning
confidence: 71%
“…As indicated earlier, in most cases, the particle size and the long diameter of clusters of enhanced STF increase with the addition of ZnO. Recently, Grover, [ 41 ] Li [ 42 ] and Lu [ 43 ] suggested that the maximum viscosity decreases with the increase of nanoparticle size in the same volume fraction. The first reason was that the number of nanoparticles in the suspension decreased with the increase of the particle size.…”
Section: Resultsmentioning
confidence: 71%
“…S9, ESI †) along with Zn 2+ well attached with the PTFE network. Further based on the previous reports, [43][44][45][46] FS as a rigid hydrophilic filler has a reinforcing effect on the mechanical properties due to its abundant -OH functional group and high hardness. Second, with regard to the electrical properties, as can be seen from Fig.…”
Section: Papermentioning
confidence: 80%
“…The benefit of shear thickening behavior of fluids in the mechanical and ballistic applications was reported in numerous studies [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. For these studies, a thickening ratio is taken into account in the efficiency of an STF [ 46 ].…”
Section: Theoretical Basismentioning
confidence: 99%